1988
DOI: 10.1007/bf01064271
|View full text |Cite
|
Sign up to set email alerts
|

Bayes' theorem in the trial process: Instructing jurors on the value of statistical evidence.

Abstract: The use of statistics and probabilities as legal evidence has recently come under increased scrutiny. Judges' and jurors' ability to understand and use this type of evidence has been of special concern. Finkelstein and Fairley (1970) proposed introducing Bayes' theorem into the courtroom to aid the fact-finder evaluate this type of evidence. The present study addressed individuals' ability to use statistical information as well as their ability to understand and use an expert's Bayesian explanation of that evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 38 publications
3
50
0
Order By: Relevance
“…These studies have consistently found that judgments of guilt varied appropriately (Faigman & Baglioni, 1988;Goodman, 1992;Smith et al, 1996). In every case people gave more weight to the forensic evidence (greater shifts in estimated chances of guilt) when the RMP was low than when it was higher.…”
Section: Sensitivity To the Strength Of Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…These studies have consistently found that judgments of guilt varied appropriately (Faigman & Baglioni, 1988;Goodman, 1992;Smith et al, 1996). In every case people gave more weight to the forensic evidence (greater shifts in estimated chances of guilt) when the RMP was low than when it was higher.…”
Section: Sensitivity To the Strength Of Evidencementioning
confidence: 99%
“…Research has generally found that simulated jurors are less responsive to forensic evidence than Bayesian models indicate they should be (Thompson & Schumann, 1987;Faigman & Baglioni, 1988;Goodman, 1992;Smith et al, 1996;Schklar & Diamond, 1999;Nance & Morris, 2002, 2005Martire et al, 2013Martire et al, , 2014; for reviews of the early studies see Koehler, 2001;Kaye & Koehler, 1991;Thompson, 1989). But Thompson, Kaasa, and Peterson (2013) recently questioned whether jurors always underutilize forensic evidence relative to Bayesian norms.…”
Section: Logical Coherencementioning
confidence: 99%
“…They got the same result when they gave participants the prior assessment of guilt. Faigman and Baglioni (1988) and, in a different setting of liability for personal injury, Bornstein (2004) got this result as well. Other references are Edwards (1968) and Saks and Kid (1980).…”
Section: Overview Of Literaturementioning
confidence: 61%
“…Instead, the evidence suggests that people have a generally poor understanding of probabilities and statistics; tend to confuse likelihoods and posterior beliefs (as in the prosecutor and defence attorney fallacies) 20 ; and tend toward an under-valuing of the evidence as compared to normative (i.e. Bayesian) models [21][22][23][24] . Moreover, meta-analyses of risk communication literature 25 in addition to numerous studies focusing specifically on probabilistic expressions in court [26][27][28][29] suggest that decision-makers are sensitive to the form in which statistics are presented and have a preference for natural frequencies or event rates.…”
Section: Probabilistic Information and Belief Updatingmentioning
confidence: 99%